Estudo da eficácia da Aloe vera como crioprotetor vegetal na criopreservação de espermatozoide caprino. - Farias, Camilla Flávia Avelino de (2020)
The objective of this work was to evaluate different concentrations of Aloe vera (AV) in the production of an extender of vegetable origin for the preservation of goat sperm cells. The AV was processed and submitted to qualitative characterization, pH measurement and determination of reducing sugars. After characterization, a buffer solution was prepared based on TRIS with the following parameters: A1 (TRIS, AV1 concentration, 5% glycerol); A2 (TRIS, AV2 concentration, 5% glycerol); and A3 (TRIS, AV3 concentration, 5% glycerol), subjected to osmolarity and rheology tests. Ejaculates applied to three goats were homogenized and applied to the freezing protocol, divided into four experimental groups (GC - diluter based on TRIS-yolk; AV1, AV2 and AV3). After thawing, seminal samples were evaluated for kinetics (Computer- Assisted Sperm Analysis), integrity of plasmatic and acrossomal membranes, mitochondrial membrane potential and levels of reactive intracellular oxygen species (flow cytometry). AV showed terpenoids, esters and saponin, acid pH (5.5) and high amount of reducing sugars (1g / L). The osmolarity of the CG and the AV groups keep the next ones, however, the higher the percentage of AV, the lower the osmolarity. There is no clinical trial, viscosity reduction with increased temperature and AV groups that obtain lower viscosity when compared to the CG. In the analysis of goat semen subjected to freezing, the AV groups showed less (P <0.05) total and progressive mobility compared to fresh semen and GC. There was a reduction (P <0.05) in line speed and the average speed of sperm movement between GC and AV groups, as well as a reduction (P <0.05) of the oscillation index only in group A2. For sperm membranes, group A3 has a greater (P <0.05) mitochondrial potential than the other groups and no difference was observed (P> 0.05) between groups for the other tests performed, as far as kinetics and integrity of membranes. A seminal extender requires osmolarity and pH, energy source and cryoprotectants, and these requirements are provided by the AV-based extender, which also exhibits antioxidant substances (terpenoids) and lipids (sterols), which provide cell protection at low temperatures. Motility is a necessary parameter for the cell to reach or hide and close it. The AV groups demonstrated water motility values of those observed in the GC, due to their composition, which presents complex polysaccharides that form a mesh and recover these sperm. The higher the percentage of AV, the greater the proportion of these polysaccharides. This is reflected in the greater potential of the mitochondrial membrane in group A3, since the sperm increases or wastes to try to move through the medium. The AV groups were able to maintain the integrity of the membranes applicable to the GC, as well as the levels of ROS produced. This condition is possible due to bioactive substances present in AV, which allows cell protection during cell freezing. Based on not exposed, conclude that an Aloe vera can be a substitute for the common extenders used in freezing goat sperm, however, more studies are needed to increase sperm mobility after thawing.